If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2) + 3y = -6 Multiply 2 * 2 4 + 3y = -6 Solving 4 + 3y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3y = -6 + -4 Combine like terms: 4 + -4 = 0 0 + 3y = -6 + -4 3y = -6 + -4 Combine like terms: -6 + -4 = -10 3y = -10 Divide each side by '3'. y = -3.333333333 Simplifying y = -3.333333333
| 2(1)+3y=-6 | | 4y+1=15+3y | | 5=5(x-4)-(x-5) | | 7-3x=33 | | 36=5x+11 | | 4(y+7)-6y=38 | | 2(-1)+3y=-6 | | 4y+1=15y+3y | | 3/8*4/7 | | 4(2x+3)-3(x+3)=2(3x-2)+(x-2) | | F=9/5(100)+35 | | 2(-2)+3y=-6 | | 15x^2-1=2x | | x*5=45 | | 3-19=-8 | | 1x-5=23 | | 86=m+33 | | 4*5/8 | | 6-2t=3t-4 | | -x/11=9 | | -x/3+26=15 | | 6x-2=23 | | w/11-14/22 | | 354.08=180+0.64x | | 1/2(x+6)+1=-5 | | 4x5/8 | | 25x+11x=27.50 | | g^2-6g-40=0 | | n-g(n+r)2= | | k=(-12z+20)/(-4z+26) | | 16/7-4.8/h | | 6t-8=52 |